Europe and Indo-Pacific in the World Order Transition - Fulvio Attinà (Romanian Journal of European Affairs, 2025)
The current transition of the world order involves clusters of states with different views on how to address global challenges. The article focuses on the relations between Europe and Indo-Pacific Asia, which are of primary concern to EU policymakers. The article is an account of the specificities and similarities of these international regions that have significant potential for the evolution of the world order. The article explains that the membership in existing or emerging coalitions is at the root of the different positions adopted by China and the EU member states. The conclusions emphasise that the transition process requires states in both regions to formulate world order projects based on global consensus.